2018
DOI: 10.1007/s00244-017-0500-z
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Total Suspended Particles (TSP) by Positive Matrix Factorization (PMF) and Chemical Mass Balance (CMB) Modeling in Ahvaz, Iran

Abstract: There is a compelling need for apportionment of pollutants' sources to facilitate their reduction through proper management plans. The present study was designed to determine the contribution of each possible source of total suspended particles in Ahvaz's ambient air using positive matrix factorization (PMF), chemical mass balance (CMB), and the SPECIATE database. The sampling program undertaken followed EPA's guidelines and finally resulted in 74 samples. The concentration of 33 elemental and 10 ionic species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…PM 2.5 was collected on 47 mm quartz filters at a flow rate of 20 L/min. Before sampling, the filters were washed with doubledistilled water, and placed in an oven at 100-105°C for 2 h [93]. After sampling, the filters were stored in aluminum foil at − 10°C to prevent evaporation and photodegradation of PM components.…”
Section: Exposure Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PM 2.5 was collected on 47 mm quartz filters at a flow rate of 20 L/min. Before sampling, the filters were washed with doubledistilled water, and placed in an oven at 100-105°C for 2 h [93]. After sampling, the filters were stored in aluminum foil at − 10°C to prevent evaporation and photodegradation of PM components.…”
Section: Exposure Periodsmentioning
confidence: 99%
“…To determine the elemental composition of PM, onehalf of filters were shredded, and put into a Teflon container with 2.5 ml of concentrated of HClO 4 (70%) and 2.5 ml HNO 3 (69%). Samples were heated at 170°C for 4 h, and dried on a hot plate at 100 C. After adding 2.5 ml of double-distilled water and 2.5 ml of HNO 3 ,the samples were shaken at 180 rpm for 30 min [93]. Finally, the samples were filtered through Whatman No.…”
Section: Exposure Periodsmentioning
confidence: 99%
“…Filters were changed every 2 days (48 hour samples). Before the sampling, the lters were washed with doubledistilled water, and placed in an oven at 100-105 °C for 2 hours [97]. After sampling and for preventing of evaporation, and photodegradation of PM components, the lters were stored in aluminum foil at -10 °C.…”
Section: Exposure Periodsmentioning
confidence: 99%
“…The lters were shredded, and put into a Te on container with 2.5 ml of concentrated of HClO 4 (70%), and 2.5 ml HNO 3 (69%), heated at 170 °C for 4 hr, and taken to dryness on a hot plate at 100 . Then 2.5 ml of double-distilled water and 2.5 ml of HNO 3 was added and, the samples were shaken at 180 rpm for 30 min [97]. Finally, the solutions were ltered through a Whatman No.…”
Section: Exposure Periodsmentioning
confidence: 99%
“…Factor 6 was mainly dominated by secondary inorganic ions (e.g., SO 4 2− , NO 3 − , and NH 4 + ) with moderate OC, which was typical for secondary formation and included in a secondary category [61]. Na + had relatively high loading in factor 6 probably because secondary source was mixed with some transported marine aerosol [62,63], especially in EP2. The 72-h back trajectories showed that air masses originated from marine atmosphere before reaching the receptor (Figure 4).…”
Section: Primary Sources Of Wsoc Determined By the Pmf Modelmentioning
confidence: 99%